2008
DOI: 10.1038/mp.2008.63
|View full text |Cite
|
Sign up to set email alerts
|

Altered calcium homeostasis in autism-spectrum disorders: evidence from biochemical and genetic studies of the mitochondrial aspartate/glutamate carrier AGC1

Abstract: Autism is a severe developmental disorder, whose pathogenetic underpinnings are still largely unknown. Temporocortical gray matter from six matched patient-control pairs was used to perform post-mortem biochemical and genetic studies of the mitochondrial aspartate/glutamate carrier (AGC), which participates in the aspartate/malate reduced nicotinamide adenine dinucleotide shuttle and is physiologically activated by calcium (Ca(2+)). AGC transport rates were significantly higher in tissue homogenates from all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(150 citation statements)
references
References 60 publications
9
138
1
2
Order By: Relevance
“…Another vulnerability gene, MET, was identified by Campbell and Levitt collaborating with our group for the genetic studies involved in this project [80,81]. In addition, we have identified other new vulnerability genes and confirmed associations initially reported in other samples for several genes, including ADA [82], APOE [83], HOXA1 [84,85], ITG-B3 [86], PON1 [87], PRKCB1 [88], SLC6A4 [89,90], SLC-25A12 [91].…”
Section: Our Roadmap: Methodological Issues and Strategiessupporting
confidence: 54%
See 1 more Smart Citation
“…Another vulnerability gene, MET, was identified by Campbell and Levitt collaborating with our group for the genetic studies involved in this project [80,81]. In addition, we have identified other new vulnerability genes and confirmed associations initially reported in other samples for several genes, including ADA [82], APOE [83], HOXA1 [84,85], ITG-B3 [86], PON1 [87], PRKCB1 [88], SLC6A4 [89,90], SLC-25A12 [91].…”
Section: Our Roadmap: Methodological Issues and Strategiessupporting
confidence: 54%
“…(v) Most ASD brains display significant neuroinflammation [98], excessive calcium levels [91], presence of oxidative stress [91], and an overexpression of immune genes even as early as at 4 years of age [99];…”
Section: Conclusion: Clinical and Research Perspectivesmentioning
confidence: 99%
“…Two recent studies have reported mitochondrial dysfunction in autism. Post-mortem samples showed increased mitochondrial metabolism and oxidised mitochondrial proteins in the brains of six people with autism compared with controls (Palmieri et al 2010). Another study showed that 11/21 patients with ASD had definite mitochondrial disease while the rest had probable mitochondrial disease (Weissman et al 2008).…”
Section: Mitochondrial Diseasementioning
confidence: 99%
“…excessive intracellular Ca 2+ spikes can in turn interfere both with neurodevelopment and with energy production, modulating the activity of the mitochondrial aspartate-glutamate carrier AGC1. Interestingly, also the SlC25A12 gene, which encodes for AGC1, encompasses genetic variants able to influence disease risk in autism (Palmieri et al, 2010). Genetic vulnerability at the ATP2B2 and SLC25A12 loci could be exacerbated by prenatal environmental exposure to PCBs, important endocrine disruptors also able to promote Ca 2+ entry from the extracellular space, and Ca 2+ release from the endoplasmic reticulum (Pessah et al, 2010).…”
Section: Clinical Perspectives Of Developmental Neurotoxicitymentioning
confidence: 99%